Understanding and Addressing the Lack of Clinical Trial Enrollment Among Adolescents With Cancer - Tai, Eric (Pediatrics, 2014)
Despite overall improvement in survival, morbidity, and quality of life of US patients with cancer, this progress is less prevalent in the population of adolescent and young adult patients with cancer, including those between the ages of 15 and 19 years. Evidence suggests that participation in clinical trials is associated with better survival outcomes among children and adolescents with cancer; however, adolescents have lower clinical trial participation rates compared with younger age cohorts. To better understand the unique concerns among adolescent patients with cancer, the Division of Cancer Prevention and Control at the Centers for Disease Control and Prevention convened a workgroup of researchers and health care providers in the field of adolescent and young adult oncology and cancer survivorship to examine the barriers and challenges limiting the participation of adolescents in clinical trials and to define ways to improve upon these concerns. This article summarizes the activities of the workgroup and their suggestions for enhanced accrual.